PENGARUH MODEL DISCOVERY LEARNING PADA MATERI SIKLUS AIR TERHADAP PENINGKATAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V SEKOLAH DASAR - Anantasya, Adisti; Hadnistia Darmawan, Nurani; Sodiah, Siti; Solihat, Ai; Cindy, Nova (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low critical thinking skills of elementary school students on water cycle material. The purpose of this study was to determine the effect of the Discovery Learning model on improving the critical thinking skills of fifth-grade students at SDN 1 Cimanggu on water cycle material. This research employed a quantitative approach with a pre-experimental one-group pretest-posttest design. The population consisted of all fifth-grade students of SDN 1 Cimanggu in the 2025/2026 academic year, totaling 30 students, and all of them were selected as the sample through total sampling. The research instrument was a critical thinking essay test consisting of 10 items. Data were analyzed using normality testing, paired sample t-test, and N-gain analysis with SPSS version 23. The results showed that the mean pretest score of 67.13 increased to 88.37 in the posttest. The paired sample t-test showed a significance value of 0.000 < 0.05, indicating a significant difference between pretest and posttest scores. The N-gain result of 0.62 was categorized as moderate. Therefore, the Discovery Learning model had a significant effect on improving students’ critical thinking skills in water cycle material.